+0  
 
0
571
4
avatar

(2,87 * 10-6) * (0,32 * 10-6) * (0,013 * 10-6) = ?

 12.10.2017
bearbeitet von Gast  12.10.2017
 #1
avatar+109 
0

Hallo,

 

(2,87 * 10-6) * (0,32 * 10-6) * (0,013 * 10-6) = ?

 

 

(2,87 * 10-6) * (0,32 * 10-6) * (0,013 * 10-6) = 2,87 * 0,32 * 0,013 * 10^-18 = 0,0119392 * 10^-18 = 11,9392 * 10^-20

 

Liebe Grüße

 12.10.2017
 #3
avatar
+1

Ist es nicht  1,19 * 10-20 ????

Gast 12.10.2017
 #2
avatar
+1

Vielen Dank für die schnelle Antwort !

 12.10.2017
 #4
avatar+8459 
0

(2,87 * 10-6) * (0,32 * 10-6) * (0,013 * 10-6) = ?

 

(2,87 * 10-6) * (0,32 * 10-6) * (0,013 * 10-6) = 1,19392 * 10 - 20

 

laugh   !

 12.10.2017

18 Benutzer online